Impaired thrombin-induced platelet activation and thrombus formation in mice lacking the Ca2+-dependent tyrosine kinase Pyk2 - Canobbio, I.; Cipolla, L.; Consonni, A.; Momi, S.; Guidetti, G.; Oliviero, B.; Falasca, Marco; Okigaki, M.; Balduini, C.; Gresele, P.; Torti, M. (2013)
In the present study, we used a knockout murine model to analyze the contribution of the Ca2+-dependent focal adhesion kinase Pyk2 in platelet activation and thrombus formation in vivo. We found that Pyk2-knockout mice had a tail bleeding time that was slightly increased compared with their wild-type littermates. Moreover, in an in vivo model of femoral artery thrombosis, the time to arterial occlusion was significantly prolonged in mice lacking Pyk2. Pyk2-deficient mice were also significantly protected from collagen plus epinephrine-induced pulmonary thromboembolism. Ex vivo aggregation of Pyk2-deficient platelets was normal on stimulation of glycoprotein VI, but was significantly reduced in response to PAR4-activating peptide, low doses of thrombin, or U46619. Defective platelet aggregation was accompanied by impaired inside-out activation of integrin αIIbβ3 and fibrinogen binding. Granule secretion was only slightly reduced in the absence of Pyk2, whereas a marked inhibition of thrombin-induced thromboxane A2 production was observed, which was found to be responsible for the defective aggregation. Moreover, we have demonstrated that Pyk2 is implicated in the signaling pathway for cPLA2 phosphorylation through p38 MAPK. The results of the present study show the importance of the focal adhesion kinase Pyk2 downstream of G-protein–coupled receptors in supporting platelet aggregation and thrombus formation.